Biogeography of Phallusia nigra: Is it really black and white? - Vandepas, L. E.; Oliveira, L. M.; Lee, S. S.; Hirose, E.; Rocha, R. M.; Swalla, B.J. (The Biological Bulletin, 2015)
Ascidians (Chordata, Tunicata) are an important group for the study of invasive species biology due to rapid generation times, potential for biofouling, and role as filter feeders in an ecosystem. Phallusia nigra is a putative cosmopolitan ascidian that has been described as introduced or invasive in a number of regions in the Pacific Ocean (India, Japan, and Hawaii) and in the Mediterranean. The taxonomic description of P. nigra includes a striking smooth, black tunic and large size. However, there are at least two similar Phallusia species—P. philippinensis and P. fumigata—which also have dark black tunics and can be difficult to discern from P. nigra. The distribution of P. nigra broadly overlaps with P. philippinensis in the IndoPacific and P. fumigata in the Mediterranean. A morphological comparison of P. nigra from Japan, the Caribbean coast of Panama, and Brazil found that Atlantic and Pacific samples were different species and led us to investigate the range of P. nigra using morphological and molecular analyses. We sequenced 18S rDNA and cytochrome oxidase B of individual ascidians from the Red Sea, Greece, Singapore, Japan, Caribbean Panama, Florida, and Brazil. Our results show that identification of the disparate darkly pigmented species has been difficult, and that several reports of P. nigra are likely either P. fumigata or P. philippinensis. Here we include detailed taxonomic descriptions of the distinguishing features of these three species and sequences for molecular barcoding in an effort to have ranges and potential invasions corrected in the ascidian literature.